The linguistic cycle language change and the language faculty - Gelderen, Elly van. (New York ; Oxford : Oxford University Press, 2011)
In this volume, Elly van Gelderen examines the linguistic cycle and describes how it offers a unique perspective on the language faculty. Each chapter provides data on a separate cycle from a myriad of languages.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Linguistic change